Football beats hypertension: results of the 3F (Fit&Fun with Football) study - Schrader, Bastian; Schrader, Joachim; Vaske, Bernhard; Elsaesser, Albrecht; Haller, Hermann; Del Vecchio, Alessandro; Koziolek, Michael; Gehlenborg, Eugen; Lueders, Stephan (Journal of Hypertension, 2021)
Objective(s): Football as the most popular sport could improve insufficient physical activity in patients with cardiovascular risk factors. A modified 'healthy' football training format could motivate hypertensive patients to return to sport and improve risk factors. Methods: The 3F study: 'Fit and Fun with Football' a prospective interventional study with 1 year follow-up. Football group: n = 103, structured 'health'-football training (1x/week, 90 min) led by Deutscher Fussball Bund-licensed football coaches. Hypertensive patients at least 45 years who have not exercised for several years were compared with a control group (n = 105). Primary study objective: Reduction of office (OBP) and/or 24-h ambulatory blood pressure (BP) monitoring (ABPM) and/or reduction of number or dosage of antihypertensive medication. Main results: OBP values decreased significantly in the football group from 142.6/87.9 to 130.8/81.8 mmHg (P < 0.001), in the control group the values increased slightly (NS). ABPM values decreased significantly in the football group, while a slight increase was found in the control group. At the end of the study, the mean values in the football group of both OPB (P < 0.001) and ABPM (systolic P < 0.001, diastolic P = 0.017) were significantly lower than in the control group. Significantly more people in the football group were able to reduce antihypertensive patients than in the control group (football group:16, control group:6), while more participants in the control group intensified antihypertensive therapy (football group:3, control group:14) (P < 0.001). Among the secondary endpoints, there was a weight loss of 3 kg in the football group and an increase of 1.7 kg in the control group (P < 0.001). Conclusion: Offering modified 'healthy' football-training to middle-aged hypertensive patients can lead to better BP control and a reduction of antihypertensive medication. Therefore, the offer of 'health football' should be established and supported by clubs, insurances and authorities.
CRIS-Team WoS Importer:2021-10-15